Review of beyond liberal democracy - TAN, Sor-hoon (Institutional Knowledge at Singapore Management University, 2011)
Beginning with an account of Ronald Dworkin’s two-week visit toChina in 2002 as an example of how “uniquely parochial” post–WorldWar II Western liberal democratic theory and theorists have been,Daniel A. Bell proceeds to examine how theories of human rights,democracy, and capitalism (“main hallmarks of liberal democracy”)have become substantially modified when transmitted to East Asiansocieties. Bell brings a wealth of interesting material to support hisargument that “[w]hat is right for East Asians does not simply involveimplementing Western-style political practices when the opportunitypresents itself; it involves drawing upon East Asian political realitiesand cultural traditions that are defensible to contemporary EastAsians” (p. 8). This review focuses on the middle section on democ-racy and deals only briefly with the first and last sections.